ผลการจัดกิจกรรมการเรียนรู้ตามแนวคิดจิตตปัญญาศึกษาที่ส่งผลต่อความสามารถ ในการพัฒนาหลักสูตรท้องถิ่นของนิสิตครู มหาวิทยาลัยพะเยา - Jantakoon, Jakkrit (Journal of Community Development Research (Humanities and Social Sciences); Vol 10 No 4 (2560): October-December 2017, 2017)
การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อ 1) เปรียบเทียบความรู้ในการพัฒนาหลักสูตรท้องถิ่นของนิสิตครูก่อนเรียนและหลังเรียน ด้วยกิจกรรมการเรียนรู้ตามแนวคิดจิตตปัญญาศึกษา 2) เปรียบเทียบทักษะในการเขียนหลักสูตรท้องถิ่นหลังเรียนด้วยกิจกรรมการเรียนรู้ตามแนวคิดจิตตปัญญาศึกษากับเกณฑ์ร้อยละ 75 3) ศึกษาผลการพัฒนาหลักสูตรท้องถิ่นของนิสิตครู และ 4) ศึกษาการเปลี่ยนแปลงคุณลักษณะอันพึงประสงค์ของนิสิตครู กลุ่มเป้าหมายเป็นนิสิตครูสาขาวิชาชีววิทยา ชั้นปีที่ 1 จำนวน 35 คน ได้มาโดยการเลือกแบบเจาะจง (Purposive Sampling) ใช้เวลาทดลอง 20 ชั่วโมง เครื่องมือที่ใช้ในการวิจัย ได้แก่ แผนการจัดกิจกรรมการเรียนรู้ โดยใช้แนวคิดจิตตปัญญาศึกษา แบบทดสอบวัดความรู้ในการพัฒนาหลักสูตรท้องถิ่น แบบประเมินทักษะในการเขียนหลักสูตรท้องถิ่น แบบประเมินหลักสูตรท้องถิ่น แบบบันทึกการเรียนรู้ และแบบประเมินหลังเข้าร่วมกิจกรรม (AAR) การวิเคราะห์ข้อมูลโดยใช้ค่าเฉลี่ยความเบี่ยงเบนมาตรฐาน ร้อยละ และการทดสอบค่าทีแบบไม่เป็นอิสระต่อกัน ส่วนข้อมูลเชิงคุณภาพวิเคราะห์โดยการวิเคราะห์เนื้อหา      ผลการวิจัย พบว่า      1. นิสิตครูมีความรู้ในการพัฒนาหลักสูตรท้องถิ่นหลังเรียนสูงกว่าก่อนเรียนด้วยกิจกรรมการเรียนรู้ตามแนวคิดจิตตปัญญาศึกษาอย่างมีนัยสำคัญทางสถิติที่ระดับ .05      2. นิสิตครูมีทักษะในการเขียนหลักสูตรท้องถิ่นหลังเรียนคิดเป็นร้อยละ 78.14 ซึ่งสูงกว่าเกณฑ์ร้อยละ 75 อย่างมีนัยสำคัญทางสถิติที่ระดับ .05 โดยนิสิตมีคะแนนทักษะในการเขียนจุดมุ่งหมายของหลักสูตรสูงสุด รองลงมา คือ หลักการและเหตุผล และมีคะแนนทักษะในการเขียนแนวทางการจัดกิจกรรมการเรียนรู้ต่ำสุด      3. ได้หลักสูตรท้องถิ่นที่มีคุณภาพระดับดีมากจำนวน 9 หลักสูตร คิดเป็นร้อยละ 25.71 ระดับดีจำนวน 19 หลักสูตร คิดเป็นร้อยละ 54.29 และระดับพอใช้จำนวน 7 หลักสูตร คิดเป็นร้อยละ 20.00      4. นิสิตครูตระหนักเห็นความสำคัญของหลักสูตรท้องถิ่น มีความศรัทธาต่ออาชีพครูมากขึ้น เห็นอกเห็นใจผู้อื่น มีความรับผิดชอบ และมีทักษะในการแก้ปัญหาดีขึ้น      This research aimed at: 1)comparing the student teachers’ knowledge for developing local curriculum before and after participating in learning activities based on contemplative education approach, 2) comparing the writing skills for developing local curriculum after participating in the learning activities with the criterion at 75 percent, 3)studying the effect of developing local curriculum of student teachers, and 4) studying the transforming of desired characteristics of student teachers. The participants were obtained by the purposive sampling of 35 student teachers majoring in teaching biology. The study took 20 hours. The instruments consisted of the lesson plans based on contemplative education approach, achievement test on the development of local curriculum, evaluation form assessing writing skills of the local curriculum, learning logs, and AAR evaluation form. Data analysis included mean, standard deviation, percentage, and t–test dependent samples. The qualitative data were analyzed by using content analysis.      The results revealed the following findings:      1. The student teachers’ competency for developing local curriculum after participating in learning activities based on contemplative education approach was higher than before the participation at the statistical level of .05.      2. The student teachers had the writing skills for developing local curriculum after participating in learning activities at 78.14%, which was higher than the criterion standard at 75% at the significant level of .05. Scoring of the student teachers’ writing ability of the aforementioned curriculum, the achievement scores ranked from the highest to the lowest were writings of purpose, rationale, and guidelines for learning activities.      3. After the participation, there were 9 (25.71%), 19 (54.29%) and 7 (20%) local curricula which were considered as “the most effective,” “good,” and “satisfying”, respectively.      4. The student teachers realized the importance of local curriculum. They have faith in teaching profession, respect toward other people, responsibility, and more problem-solving skills.
Keywords: developing the local curriculum, contemplative education, student teachers